IMPLEMENTING CRITICAL THINKING IN TEACHING FOREIGN LANGUAGES - Nyshanova, S.T.; Abay, K.N. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
Today, the ongoing process of humanization around the world defines new requirements for educational institutions in society. The growth of technical development and scientific information, the updating of the content of school education and the reorganization of the rules of educational institutions have led to an inevitable increase in the requirements for the professional qualifications and personality of the teacher, the personal orientation of the entire pedagogical process. Today, life itself proves the effectiveness of using innovative educational technologies to improve the educational process. Critical thinking also has an impact on students' interpersonal communication skills. By thinking critically and seeing things from different angles, students become more open and empathetic, better communicative, more inclined to collaborate with their peers, as well as to receive and discuss their ideas.
Keywords: critical thinking; teaching; technology; pedagogical process